Mitochondrial genome sequencing of a vermivorous cone snail Conus quercinus supports the correlative analysis between phylogenetic relationships and dietary types of Conus species. - Bingmiao Gao; Chao Peng; Qin Chen; Junqing Zhang; Qiong Shi (PLoS ONE)
Complete mitochondrial genome (mitogenome) sequence of a worm-hunting cone snail, Conus quercinus, was reported in this study. Its mitogenome, the longest one (16,460 bp) among reported Conus specie, is composed of 13 protein-coding genes (PCGs), 22 transfer RNA (tRNA) genes, two ribosomal RNA (rRNA) genes and one D-loop region. The mitochondrial gene arrangement is highly-conserved and identical to other reported. However, the D-loop region of C. quercinus is the longest (943 bp) with the higher A+T content (71.3%) and a long AT tandem repeat stretch (68 bp). Subsequent phylogenetic analysis demonstrated that three different dietary types (vermivorous, molluscivorous and piscivorous) of cone snails are clustered separately, suggesting that the phylogenetics of cone snails is related to their dietary types. In conclusion, our current work improves our understanding of the mitogenomic structure and evolutionary status of the vermivorous C. quercinus, which support the putative hypothesis that the Conus ancestor was vermivorous.